The politics of industrial mobilization in Russia, 1914-17 : a study of the war-industries committees - Siegelbaum, Lewis H. (London : Macmillan Press, 1983)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: oorlogsindustrie; Rusland